1996
DOI: 10.1177/106002809603000905
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy among Nursing Home Geriatric Medicaid Recipients

Abstract: To reduce the number of drugs prescribed and polypharmacy among geriatric Medicaid recipients, Louisiana's ICFs I should minimize the number of physicians and pharmacies used in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…29 Additionally, Gupta et al noted intrastate geographic variation with prescription count in Louisiana geriatric Medicaid beneficiaries. 30 Other researchers have investigated different dimensions of medication use geographic variation (e.g., inter- and intra-regional variation abroad and urban/rural variation). supp ref Moreover, although not a composite pharmacological assessment like polypharmacy, some United States data on the spatial distributions of use of specific medication classes are available.…”
Section: Discussionmentioning
confidence: 99%
“…29 Additionally, Gupta et al noted intrastate geographic variation with prescription count in Louisiana geriatric Medicaid beneficiaries. 30 Other researchers have investigated different dimensions of medication use geographic variation (e.g., inter- and intra-regional variation abroad and urban/rural variation). supp ref Moreover, although not a composite pharmacological assessment like polypharmacy, some United States data on the spatial distributions of use of specific medication classes are available.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the number of prescribed drugs increases along with the number of prescribing physicians and with the number of pharmacies visited [75]. Minimizing these numbers may decrease the risk of potentially inappropriate DDIs [76].…”
Section: Main Risk Factors For Adverse Drug Interactionsmentioning
confidence: 99%
“…The presence of multiple medical illnesses contributes to the problem of polypharmacy in the growing older population. Polypharmacy is defined as the regular daily consumption of multiple medications as well as the use of high‐risk medications and questionable dosing 3 . Polypharmacy is known to be a significant risk factor for adverse drug reactions (ADR), failed patient compliance, and increased health‐care costs 4 7 .…”
Section: Inappropriate Medications In Older People (Independent Of DImentioning
confidence: 99%